El juego y la motricidad gruesa en los niños de 4 a 5 años de la unidad educativa padre Julián Lorente ubicada en la ciudad de loja, en el período 2019-2020. - Cuenca Rosillo, Elida Enith (2021)
The present research work entitled: GAME AND GROSS MOTOR SKILLS IN CHILDREN FROM 4 TO 5 YEARS OF PADRE JULIAN LORENTE EDUCATIONAL UNIT LOCATED IN LOJA CITY, DURING THE ACADEMIC YEAR 2019-2020, had as general objective: to analyze the importance of games in gross motor skills in children from 4 to 5 years. The research design was non-experimental, with a mixed approach; the study population was made up of 17 people, that is, 16 children and 1 teacher, the methods used were: descriptive, analytical-synthetic and inductive-deductive, the technique used was the interview, which was directed to the classroom teacher, through this interview, it was possible to notice that his teaching is based on learning experiences, in addition as an instrument was used the Developmental Short Scale of Nelson Ortiz, the same one that was applied to the children of 4 to 5 years, showing a problem of gross motor skills, whose percentages were that 62.50% of the population investigated, is in the medium and alert level, that is to say, they have a low level of motor skills in relation to their chronological age, Concluding that the use of activities that promote motor development is essential, this led to the design an alternative proposal that consists of 40 children's games that will strengthen balance, coordination, body scheme and spatial-temporal structure, thus ensuring a good comprehensive development.